Let's solve the problem and show every step:
We are tasked to prove that:
∑k=1n(−1)kk2=2(−1)nn(n+1),for n=1,2,3,….
Step 1: Analyze the summation formula
The given sum is:
Sn=∑k=1n(−1)kk2.
Here, (−1)k alternates the sign of each term depending on whether k is odd ((−1)k=−1) or even ((−1)k=1). Each term in the sum is (−1)k⋅k2, where k2 is the square of the current index k.
We will use induction to prove the formula:
Sn=2(−1)nn(n+1).
Step 2: Base case (n=1)
For n=1, the summation is:
S1=∑k=11(−1)kk2=(−1)1⋅12=−1.
The right-hand side of the formula for n=1 is:
2(−1)nn(n+1)=2(−1)1⋅1⋅(1+1)=2−1⋅1⋅2=−1.
Thus, the formula holds for n=1.
Step 3: Inductive hypothesis
Assume that the formula holds for n=m, i.e.,
Sm=∑k=1m(−1)kk2=2(−1)mm(m+1).
Step 4: Inductive step (n=m+1)
We need to prove that the formula holds for n=m+1, i.e., that:
Sm+1=∑k=1m+1(−1)kk2=2(−1)m+1(m+1)((m+1)+1).
From the definition of Sm+1, we can write:
Sm+1=Sm+(−1)m+1(m+1)2.
Using the inductive hypothesis Sm=2(−1)mm(m+1), substitute Sm into the equation:
Sm+1=2(−1)mm(m+1)+(−1)m+1(m+1)2.
Step 5: Combine terms
Factor out (m+1) from the terms:
Sm+1=(m+1)[2(−1)mm+(−1)m+1(m+1)].
Simplify the bracketed expression. Rewrite (−1)m+1 as −(−1)m:
2(−1)mm+(−1)m+1(m+1)=2(−1)mm−(−1)m(m+1).
Combine the terms:
2(−1)mm−(−1)m(m+1)=2(−1)mm−2(−1)m(m+1).
Distribute (−1)m in the numerator:
2(−1)mm−2(−1)m(m+1)=2(−1)m(m−2m−2).
Simplify the numerator:
(−1)m(m−2m−2)=(−1)m(−m−2)=(−1)m(−(m+2)).
Thus:
2(−1)mm+(−1)m+1(m+1)=2(−1)m(−(m+2)).
Step 6: Final simplification
Substitute back into Sm+1:
Sm+1=(m+1)⋅2(−1)m(−(m+2)).
Simplify:
Sm+1=2(−1)m(m+1)(−(m+2)).
Distribute the negative sign:
Sm+1=2(−1)m+1(m+1)(m+2).
This matches the formula:
Sm+1=2(−1)m+1(m+1)((m+1)+1).
Thus, the formula holds for n=m+1.
Step 7: Conclusion
By induction, the formula:
∑k=1n(−1)kk2=2(−1)nn(n+1)
is true for all n=1,2,3,….
Questions for further exploration:
- What happens if the summation alternates with k3 instead of k2?
- How can this formula be derived using properties of finite series?
- What is the behavior of the series as n→∞?
- Can this result be extended to other powers of k, such as k4?
- How does this formula relate to combinatorial or geometric interpretations?
Tip:
When using induction, always verify the base case and ensure your inductive step properly accounts for the next term.